Kinerja Anggota DPRD Kabupaten Sidoarjo Periode 2014 – 2019 Terkait Peristiwa Luapan Lumpur Lapindo Sidoarjo - Mirza Pramudiasih Nirwana; Poppy Febriana (Kanal: Jurnal Ilmu Komunikasi, 2016)
This study aims to determine the news framing of online media kabarsidoarjo.com and sidoarjonews.com related to the performance of Sidoarjo Board Members Period 2014-2019. This qualitative research using Murray Edelman model framing analysis approach. The focus of the research is the online media coverage related to the performance of Sidoarjo Board Members. The data collected from online media by gathering information, observing news, translating and sorting among several news topics presented in kabarsidoarjo.com and sidoarjonews.com. Both online media has an important role for the performance of Sidoarjo board members especially in handling Lapindo mud disaster Sidoarjo. The conclusion of this framing analysis is kabarsidoarjo.com framing news about the performance of Sidoarjo board members related to handling of Lapindo mud disaster tend to give positive value, while sidoarjonews.com framing news about performance of Sidoarjo board members mostly tend to unilateral and giving a negative value for the performance of Sidoarjo board members. Most of the news sources are legislative and executive.